2022
DOI: 10.1371/journal.pone.0272934
|View full text |Cite
|
Sign up to set email alerts
|

Does previous circumcision and wealth index influence women’s attitude to discontinue the practice of female genital mutilation and cutting (FGM/C) in Ethiopia?

Abstract: Introduction understanding women’s attitudes towards female genital mutilation is an important step towards eliminating this practice. We used the 2016 Ethiopia Demographic and Health Survey (EDHS) data set to examine the relationship between wealth index, and previous history of circumcision on women’s opinions whether female genital mutilation (FGM) should be continued or stopped in Ethiopia. Methods Data from 6984 women aged 15–49 years were extracted from the 2016 Ethiopia EDHS data set. Multivariable lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Finally, another factor associated with the abandonment of female genital mutilation is the highest wealth quintile. This finding has been reported in studies in Ethiopia and Burkina Faso [15,25]. This could be explained by the fact that women's economic empowerment enables them to strengthen their decision-making power in the household, thereby resisting certain practices unfavorable to the health of women and their children.…”
Section: Discussionsupporting
confidence: 61%
See 1 more Smart Citation
“…Finally, another factor associated with the abandonment of female genital mutilation is the highest wealth quintile. This finding has been reported in studies in Ethiopia and Burkina Faso [15,25]. This could be explained by the fact that women's economic empowerment enables them to strengthen their decision-making power in the household, thereby resisting certain practices unfavorable to the health of women and their children.…”
Section: Discussionsupporting
confidence: 61%
“…This shows that it takes tremendous efforts from stakeholders to abandon female genital mutilation in Africa. Studies on the factors associated with female genital mutilation have shown that sociodemographic variables such as age, education, ethnicity, and wealth quintile are associated with female genital mutilation [14,15].…”
Section: Socio-demographic Characteristicsmentioning
confidence: 99%